Searching Ability of Pupal Parasitoid, Dirhinus giffardii (Silvestri) on Bactrocera zonata (Saunders) at Various Depths of Plant Debris - S. Shahzad Ali; Irshad Ali Rattar; Syed Sohail Ahmed; Aslam Bukero; Huma Rizwana; Shahnaz Naz; Munawar Ali Shah Bukhari; Taj Muhammad Rattar (Journal of Basic & Applied Sciences, 2016)
The present study was carried out to determine the searching ability of pupal parasitoid, Dirhinus giffardii of Bactrocera zonata in the Bio Control Research Laboratory, | department of Entomology, SAU, Tandojam, at temperature 27 ± 1ºC and 60 ± 5% relative humidity. Adults of fruit fly were fed with water, sugar and needo milk powder, whereas, Dirhinus giffardii were fed with honey and water solution. Ten days old D. giffardies were used against 20 pupae of Bactrocera zonata in the experiment and data recorded on parasitized pupae and un-parasitized pupae after 24, 48, 72 and 96 hours. The results in all treatments indicates that highest parasitized pupae were at peak level of (16.66) after 72 hours age of pupae on the depth of 0 cm in plant debris followed by 4 cm depth (16.33), whereas lowest parasitized pupae were recorded at 5cm depth (13.66) after 72 hours of age inside plant debris. Likewise, the highest un-parasitized pupae were at peak level of (14.00) after 24 hours of age of pupae on the depth of 3cm in plant debris followed by 1cm depth (13.00), whereas lowest un parasitized pupae were recorded at 4cm depth (11.66) after 24 hours of age inside plant debris. The analysis of variance indicated that there wasno significant difference among the parasitized and unparasitized pupae of flies in the different depths of plant debris and age intervals (P<0.05). It is concluded that the highest parasitized pupae were determined at plant debris of 0 cm, followed by 2cm, 5cm, 4cm, 1cm, and 3cm, respectively. In case of age intervals the highest parasitized pupae were recorded after 72 hours old pupae followed by 48 hours, 96 hours and 24 hours, respectively..